EXPLORING THE INTEGRATION OF TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE (TPACK) IN ONLINE TEACHING AMONG EFL LECTURERS - Endang Darsih; Vina Agustiana; Wulan Rahmatunisa (University of Kuningan, 2023)
This study is conducted based on the consideration of the importance of technology literacy for lecturers in online teaching. The purpose of this study was to find out the TPACK (Technological Pedagogical Content Knowledge) overview of English lecturers in online teaching. In particular, this study analyzed the level of TPACK along with the TPACK forming components of 3 English lecturers. This research applied a mixed method by implementing a concurrent embedded design. This study was conducted at Kuningan University by involving 3 lecturers who teach General English subject in Faculty of Teacher Training and Education, Kuningan University. Since TPACK is knowledge that integrates three basic knowledge; content knowledge (CK), pedagogical knowledge (PK) and technological knowledge (TK), so in collecting data, there are 3 instruments that were used, namely self-report questionnaires, performance assessments and observations. With regard to the TPACK level of English language education lecturers, the results of the analysis show that all of the English lecturers are described as adequate and high in most of the domains concerned in this study such as CK, PCK, TCK, TPK, and TPACK. However, they describe themselves as high in two domains; Technological Knowledge (TK), and Pedagogical Knowledge (PK). This is in line with the results of lesson plans analysis and observation of lecturers’ real teaching which refers to a high level of technology integration.